IMPROVEMENT OF THE FINANCIAL STATEMENT BASED ON THE REQUIREMENTS OF INTERNATIONAL STANDARDS - Jumayeva Mahkamtosh Shavkatovna (PEDAGOGS, 2024)
In our country, the number of companies preparing financial reports on the basis of their financial statements is increasing. Because it will be possible to achieve an increase in the transparency of financial reporting only through the transition to IFRS. Therefore, the use of documents developed by international organizations as well as advanced instruments and experiences is one of the urgent issues on the agenda. In this article, the issues of transition to international standards of financial reporting in Uzbekistan and the problems of transition to international standards of financial reporting and ways to overcome them are studied in detail.